Influence of Infection Origin, Type of Sampling, and Weather Factors on the Periodicity of Some Infectious Pathogens in Marseille University Hospitals, France - Lanceï Kaba; Audrey Giraud-Gatineau; Philippe Colson; Pierre-Edouard Fournier; Hervé Chaudet (Bacteria)
This study aimed at systematically exploring the seasonalities of bacterial identifications from 1 February 2014 to 31 January 2020 in hospitalized patients, considering the infectious site and the community-acquired or hospital-associated origin. Bacterial identifications were extracted from the data warehouse of the Institut Hospitalo-Universitaire Mediterranée Infection surveillance system, along with their epidemiological characteristics. Each species’ series was processed using a scientific workflow based on the TBATS time series model. Possible co-seasonalities were researched using seasonal peak clustering and series cross-correlations. In this study, only the 15 most frequent species were described in detail. The three most frequent species were Escherichia coli, Staphylococcus aureus, and Staphylococcus epidermidis, with median weekly incidences of 145, 74, and 39 cases, respectively. Samplings of S. aureus and E. coli follow the same seasonal dynamics. S. aureus hospital-associated infections exhibited a significant association with temperature, humidity, and pressure change, whereas community-acquired infections were only associated with precipitations. More seasonal peaks were observed during the winter season. Among the 15 peaks of this seasonal maximum, 6.7% came from blood (Klebsiellia oxytoca) and 13.3% from respiratory specimens (E. coli and S aureus). Our results showed significant associations of periodicity between pathogens, origin of infection, type of sampling, and weather drivers.